Estimating and testing CES production-functions on Irish 12-sector input-output data - Henry, E.W. (Economic & Social Studies, 1987)
Irish input-output data are used to estimate and test CES production functions for each of 12 sectors having 2 groups of input costs. The objective is to generalise input-output analysis to allow for price effects and technical change. However, the CES model is not found compatible with the data and, indeed, is less so than the traditional Leontief model. The analysis indicated the desirability of looking at alternative models, but the paucity of data prevented this.
Keywords: Input-output analyses - Ireland; Sociology